Dynamics of Abies spectabilis in Relation to Climate Change at the Treeline Ecotone in Langtang National Park - Gaire, Narayan P; Dhakal, Yub R; Lekhak, Harish C; Bhuju, Dinesh R; Shah, Santosh K (Nepal Journal of Science and Technology, 2012)
This paper is aimed to study the tree line dynamics of Himalayan silver fir (Abies spectabilis D. Don) based on its tree-ring data and age stand distribution at Langtang National Park, Central Nepal. Climatic response on radial growth, recruitment of A. spectabilis and its age distribution are carried out. The average tree density of the species in the study area (total 48 plots of 20 m x 20 m) was 236 no/ha while that for sapling and seedling in the study area was 255 and 350 no/ha, respectively. The stand character and age distribution of the species showed a high level of recruitment in the recent decades, with decreased in average age along with increased altitude. Tree-growth climate relationship showed negative response with temperature of March-May. Upward advancement of tree line is expected in the coming recent decades though not necessarily uniform through the line. DOI: http://dx.doi.org/10.3126/njst.v12i0.6506 Nepal Journal of Science and Technology 12 (2011) 220-229